A novel structure ZnO-Fe-ZnO thin film memristor. (1st November 2018) - Santos, Y.P.; Valença, E.; Machado, R.; Macêdo, M.A.
Abstract: The memristor behavior of thin films having a multilayer Pt/ZnO/Fe/ZnO/ITO structure, deposited using RF/DC magnetron sputtering, was studied. The iron layer between the ZnO layers facilitates the change in the resistance of the device through the oxidation of the iron at the ZnO/Fe interface, thus generating oxygen vacancies and providing electrons from the redox reaction between γ-Fe2 O3 and Fe3 O4 . The main mechanisms of conduction include Poole–Frenkel emission and Fowler–Nordhein tunneling with the ion migration, oxygen vacancies, and redox reactions of iron oxides (γ-Fe2 O3 and Fe3 O4 ). The response of the device to sequential voltage pulses in terms of variation in resistance, RERASE /RWRITE ratio, retention time, and control of the resistance state, through control of the applied voltage, was also evaluated.